2014
DOI: 10.1016/j.rehab.2014.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Pain during injections of botulinum toxin in children: Influence of the localization technique

Abstract: When compared to ultrasound detection, localization by electrostimulation appears to increase the overall pain caused during injections of botulinum toxin in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Ultrasound has become a very helpful and widely used tool in pediatrics, offering a visually controlled option to potentate the accuracy of injections in children [52]. The advantages are less pain, the possibility to control the injection placement even with anatomic variations, the differentiation of neighboring structures (muscles, vessels, nerves, and bones), not requiring co-operation or sedation, and the choice of documenting the site and volume of the injected toxin [15,53]. However, ultrasound does not help in finding the MEPs.…”
Section: Techniques For Localizing Muscles and Endplate Zonesmentioning
confidence: 99%
“…Ultrasound has become a very helpful and widely used tool in pediatrics, offering a visually controlled option to potentate the accuracy of injections in children [52]. The advantages are less pain, the possibility to control the injection placement even with anatomic variations, the differentiation of neighboring structures (muscles, vessels, nerves, and bones), not requiring co-operation or sedation, and the choice of documenting the site and volume of the injected toxin [15,53]. However, ultrasound does not help in finding the MEPs.…”
Section: Techniques For Localizing Muscles and Endplate Zonesmentioning
confidence: 99%
“…Pain was evaluated immediately post-procedure using a visual analog scale and a behavior based scale (FLACC (Face, Leg, Activity, Cry, Consolability). Children and or their caregivers reported a significantly lower level of pain with procedures guided with US compared to those with E-Stim guidance [ 66 ].…”
Section: Guidance Methods For Bont Injections: Levels Of Evidencementioning
confidence: 99%
“…Also pointed out by Henzel et al [4], US guidance requires less probing and searching for the targeted muscle than EMG, which reduces the number of needle sticks and pain with the injection. Bayon‐Mottu et al [5] demonstrated that children reported more pain with ES‐guided injections than US‐guided lower extremity injections.…”
Section: Case Scenariomentioning
confidence: 99%